PENERAPAN METODE FORWARD CHAINING PADA RANCANG BANGUN APLIKASI SISTEM PAKAR DIAGNOSA PENYAKIT PADA KAMBING BERBASIS WEB - Mbati, Anastasia Day; Rada, Yustina; Abineno, Reynaldi Thimotius (Institut Teknologi dan Bisnis (ITB) Swadharma, 2025)
The research aims to design an expert system application that can be used to diagnose diseases in goats. The research was conducted in Kaliuda Village, Pahunga District, East Sumba Regency, East Nusa Tenggara Province. The forward chaining method uses the PHP programming language and MySql database. The data collection method uses interview, observation, and documentation techniques. The development of the information system uses the Waterfall method. System modelling uses UML diagrams. System testing uses black-box testing and the SUS (System Usability Scale) on ten user respondents. The black-box testing is conducted to test the functional specifications of the new system. The results show that the developed system can process and convey information data from goat disease diagnoses and can assist experts in diagnosing diseases based on the symptoms occurring in goats. The SUS evaluation results show that the system received a score of 75, indicating that the system's acceptability ranges are suitable for use. For the Grade Scale criteria, the value obtained from the system is C. And the Adjective Ratings category is